L-2-Hydroxyglutarate Protects Against Cardiac Injury via Metabolic Remodeling. Issue 7 (31st August 2022) - He, Huamei; Mulhern, Ryan M.; Oldham, William M.; Xiao, Wusheng; Lin, Yi-Dong; Liao, Ronglih; Loscalzo, Joseph
Abstract : Background: L-2-hydroxyglutarate (L2HG) couples mitochondrial and cytoplasmic energy metabolism to support cellular redox homeostasis. Under oxygen-limiting conditions, mammalian cells generate L2HG to counteract the adverse effects of reductive stress induced by hypoxia. Very little is known, however, about whether and how L2HG provides tissue protection from redox stress during low-flow ischemia (LFI) and ischemia-reperfusion injury. We examined the cardioprotective effects of L2HG accumulation against LFI and ischemia-reperfusion injury and its underlying mechanism using genetic mouse models. Methods and Results: L2HG accumulation was induced by homozygous (L2HGDH [L-2-hydroxyglutarate dehydrogenase] –/– ) or heterozygous (L2HGDH +/– ) deletion of the L2HGDH gene in mice. Hearts isolated from these mice and their wild-type littermates (L2HGDH +/+ ) were subjected to baseline perfusion and 90-minute LFI or 30-minute no-flow ischemia followed by 60- or 120-minute reperfusion. Using [ 13 C]- and [ 31 P]-NMR (nuclear magnetic resonance) spectroscopy, high-performance liquid chromatography, reverse transcription quantitative reverse transcription polymerase chain reaction, ELISA, triphenyltetrazolium staining, colorimetric/fluorometric spectroscopy, and echocardiography, we found that L2HGDH deletion induces L2HG accumulation at baseline and under stress conditions with significant functional consequences. In response to LFI or ischemia-reperfusion, L2HG accumulation shifts glucose flux from glycolysis towards the pentose phosphate pathway. These key metabolic changes were accompanied by enhanced cellular reducing potential, increased elimination of reactive oxygen species, attenuated oxidative injury and myocardial infarction, preserved cellular energy state, and improved cardiac function in both L2HGDH –/– and L2HGDH +/– hearts compared with L2HGDH +/+ hearts under ischemic stress conditions. Conclusion: L2HGDH deletion-induced L2HG accumulation protects against myocardial injury during LFI and ischemia-reperfusion through a metabolic shift of glucose flux from glycolysis towards the pentose phosphate pathway. L2HG offers a novel mechanism for eliminating reactive oxygen species from myocardial tissue, mitigating redox stress, reducing myocardial infarct size, and preserving high-energy phosphates and cardiac function. Targeting L2HG levels through L2HGDH activity may serve as a new therapeutic strategy for cardiovascular diseases related to oxidative injury.